EPC Agenda 2004-09-02 - Academic Senate:::::::::
Educational Policies Committee. Chair Report. Agenda – Approved. Minutes of 5/17/18 – Approved. President Report. Campus Budget Presentation. Stevenson Hall Remodel Update. Provost Report. Information items. Consent item: Minimal Adjustments to Program: BA/BM Music – Approved. Vice Chair Report. VP of A&F Report. VP of Student Affairs Report. Associated Students Report. Good of the Order. Group Photo.